A new orogenic gold belt in Southeast Asia: Geology, mineralogy and genesis of the Vangtat gold deposit, Southeastern Laos. Issue 1 (16th December 2021) - Bounliyong, Patthana; Arribas, Antonio; Watanabe, Yasushi; Echigo, Takuya; Wong, Henry
Abstract: The Vangtat deposit is the major gold deposit in a new orogenic gold belt discovered and developed in southeastern Laos in the past two decades. Our study of the Vangtat orogenic gold deposit shows that it formed within a convergent margin along the western segment of the Poko suture zone, which marks the collision between the Indochina Terrane and the Kontum Massif. Shear structure and greenschist facies metamorphic rocks are the main hosts for gold mineralization in the Vangtat deposit. High‐grade gold‐bearing quartz‐sulfide veins and wall rock hydrothermal alteration are genetically related, and alteration minerals consist of quartz, carbonate, graphite, white mica, chlorite, and pyrite. The study of fluid inclusions and wall rock alteration assemblages indicate that the Vangtat gold deposit was formed by an aqueous‐carbonic, low salinity, reduced, weakly alkaline to near‐neutral pH fluid, mainly composed of H2 O, NaCl, CO2, CH4, N2, H2 S, H2, O2, Si, and K. Gold was predominantly carried as a sulfide complex. The precipitation of gold is related to wall rock sulfidation and the further reduction with the carbon‐bearing host rock. The correlation between trapping temperature obtained from arsenopyrite geothermometry (360–395°C) and homogenization temperature obtained from primary fluid inclusion microthermometry (240–250°C), indicates a pressure and depth range for the Vangtat deposit of 380–420 MPa and 11–13 km, respectively. Gold appears as inclusions mainly in pyrite, and auriferous pyrite is homogeneous in textural, chemical, and sulfur isotopic composition. Auriferous pyrite δ 34 S values range from +4 to +6‰, which is compatible with the δ 34 S composition of igneous rocks. Together with cobalt/nickel ratios from the Vangtat auriferous pyrite, which are significantly greater than one (avg. 6.3), we suggest that mafic‐ultramafic rocks in the geologic basement of the Vangtat deposit are the plausible source of hydrothermal gold and sulfur. The formation of this orogenic gold deposit is associated with metamorphic dehydration and devolatilization that transported gold to the site of deposition. Abstract : The Vangtat deposit is a newly discovered orogenic gold deposit in southeastern Laos, mainland Southeast Asia. High‐grade gold (>3 g/t) bearing quartz‐sulfide vein and hydrothermal alteration is hosted by shear structure and greenschist facies metamorphic rock, in which gold is presented as inclusions mainly in pyrite and the precipitation of gold is related to the wall rock sulfidation and reduction by reaction with the carbon‐bearing host rock.